2014
DOI: 10.4103/0976-9668.136159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorhexidine chip in the treatment of chronic periodontitis

Abstract: Aims:The evaluation of clinical and specific microbiological changes associated with chlorhexidine chip in the chronic periodontitis patients.Materials and Methods:A total of 30 chronic periodontitis patients (aged 20-65 years) having pocket depth of ≥5 mm in molar teeth were selected and randomly divided into following treatment groups: Group 1 - Scaling and root planning (SRP), Group 2 - SRP along with chlorhexidine chip and Group 3 - Only chlorhexidine chip. The clinical and microbial parameters were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Periodontal disease is a complex multifactorial inflammatory oral disease categorised by destruction of periodontal tissues and loss of the connective tissue attachment. 37 , 38 , 39 Once the diagnosis is made, it must be categorised by the process of staging and grading; this is a significant change from the previous classification system. 40 Gingivitis and periodontitis are a continuum of the same inflammatory disease, and although not all patients with gingivitis will progress to periodontitis, the management of gingivitis is the primary prevention strategy for periodontitis.…”
Section: Resultsmentioning
confidence: 99%
“…Periodontal disease is a complex multifactorial inflammatory oral disease categorised by destruction of periodontal tissues and loss of the connective tissue attachment. 37 , 38 , 39 Once the diagnosis is made, it must be categorised by the process of staging and grading; this is a significant change from the previous classification system. 40 Gingivitis and periodontitis are a continuum of the same inflammatory disease, and although not all patients with gingivitis will progress to periodontitis, the management of gingivitis is the primary prevention strategy for periodontitis.…”
Section: Resultsmentioning
confidence: 99%
“…The greatest success has been with CHX, which is now considered the gold standard, against which other potential antiplaque agents are measured. [ 28 ] However, the local side effects of CHX, particularly extrinsic staining and taste aberrations, may limit its long-term use in oral hygiene products. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested that local drug delivery via CHX chip improves the advantage of scaling and root planing in the treatment of chronic periodontitis. 24 Furthermore, clinical evaluation of periodontal tissue after treatment of 40 patients by drugs containing CHX indicated that CHX should be most frequently utilized as a drug adjunct for the treatment of classic periodontitis, particularly in forms that can be administrated directly into periodontal pockets. 20…”
Section: Discussionmentioning
confidence: 99%